A (Presumably Chinese) tantric scripture and its Japanese exegesis: the Yuqi Jing 瑜祇經 and the practices of the Yogin. Issue 1 (2nd January 2022) - Dolce, Lucia
ABSTRACT: The Yuqi jing [ Sūtra of the Yogin] is often listed as one of the most important scriptures of Tantric Buddhism in East Asia, but its content and contribution to the esoteric system have so far been little understood. Traditionally regarded as a translation by Vajrabodhi, it was probably compiled in China in the late eighth century. The role that it played in Chinese Buddhism, however, remains unclear. In medieval Japan on the other hand, the scripture appears to have been rediscovered and enjoyed great fortunes. Medieval interpreters intervened on the text by articulating novel conceptual associations, often expressed through curious imagery. At the same time, a new type of initiatory abhiṣeka informed by the sūtra emerged, which engendered a distinctive discourse on the yogic identities pursued by a tantric practitioner. What spurred such sudden interest in the Yuqi jing in medieval Japan? What did Japanese exegetes read into the text? This article addresses these issues by exploring 'canonical' commentaries and unpublished initiatory documents that have recently come to light in temple archives.